Analisis Ekowisata dan Budaya Alam Santosa Sebagai Learning Center di Kecamatan Cimenyan Kabupaten Bandung - Rasyid, Sayyidah; Cahyanto, Tri (ECOTAS, 2023)
The establishment of a Learning Center on Ecotourism and Natural Culture of Santosa encourages the development of local policy insights, contributing to the development of national cultural values. Included in the Santosa Nature Ecotourism and Culture private area which provides coffee shop facilities, lodging places with themes that have a strong Sudanese cultural nuance. The purpose of this study was to determine the factors of establishing a Learning Center in a culture-based tourism village. This journal analyzes descriptively qualitatively, filling out questionnaires in the surrounding community, and the parameters seen include attractions, amenities, and accessibility presented in the SWOT analysis. The results of the factors that influenced the establishment of Ecotourism and Culture Alam Santosa to become a Learning Center were influenced by internal and external factors with the strongest factors being the attractions of diverse cultural infrastructure and the trust that was woven with a strong community.